Therapeutic approaches for improving cognitive function in the aging brain - Chen, Lingmin; Jiao, Jiao; Zhang, Yonggang (Frontiers in Neuroscience, 2022)
The rapid aging of populations around the world has become an unprecedented challenge. Aging is associated with cognitive impairment, including dementia and mild cognitive impairment. Successful drug development for improving or maintaining cognition in the elderly is critically important. Although 4 drugs for improving cognition using in Alzheimer's disease have been approved, a variety of potential drugs targeting age-related cognitive impairment are still in development. In addition, non-pharmacological interventions, including cognition-oriented treatments, non-invasive brain stimulation physical exercise, and lifestyle-related interventions, have also been suggested as cognitive enhancers in the last decade. In this paper, we reviewed the recent evidence of pharmacological and non-pharmacological interventions aimed at improving or maintaining cognition in the elderly.